Which of the following equations could be used to solve the given equation?
9x + 26 + 7x - 17 = 2x + (-3x) + 5x
16x + 9 = 0
16x + 9 = 4x
16x + 11 = 4x

Question

Asked 6/28/2013 3:00:10 AM

Updated 6/22/2014 7:17:31 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/22/2014 7:14:45 PM]

debnjerry|Points 48126|

jher000|Points 8061|

uxiali|Points 1587|

zcapzbaby|Points 110|

andrewpallarca|Points 22893|

andrewpallarca|Points 22893|

rugmaker|Points 3178|

theresearcher|Points 2086|

johannakix8|Points 10|

j3m|Points 172|

japs2310qa|Points 1979|

jwolf0808|Points 25|

japs2310qa|Points 1979|

Question

Asked 6/28/2013 3:00:10 AM

Updated 6/22/2014 7:17:31 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/22/2014 7:14:45 PM]

Rating

3

5x + 2(x - 3) = -2(x - 1)

5x + 2x - 6 = -2x + 2

7x - 6 = -2x + 2

7x + 2x = 2 + 6

9x = 8

x = 8/9

5x + 2x - 6 = -2x + 2

7x - 6 = -2x + 2

7x + 2x = 2 + 6

9x = 8

x = 8/9

Added 6/22/2014 7:14:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/22/2014 7:15:27 PM]

3

6 - (3x + 10) + 4(2 - x) = 15

6 - 3x - 10 + 8 - 4x = 15

4 - 7x = 15

-7x = 15 - 4 = 11

x = -11/7

6 - 3x - 10 + 8 - 4x = 15

4 - 7x = 15

-7x = 15 - 4 = 11

x = -11/7

Added 6/22/2014 7:16:20 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/22/2014 7:26:40 PM]

3

3(x + 2) = 12

3x + 6 = 12

3x = 12 - 6 = 6

x = 6/3 = 2

3x + 6 = 12

3x = 12 - 6 = 6

x = 6/3 = 2

Added 6/22/2014 7:17:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/22/2014 7:26:54 PM]

27,372,317

questions answered

There are no comments.